Single-band and dual-band microstrip filter-antenna for wireless applications - Khudhaier, Mohammed Kadhim (2017)
In conventional narrow band radio frequency (RF) systems, all RF components are designed separately and all the input/output ports are matched to a standardized value typically 50 Ω. For simplicity and miniaturization, it is preferable to integrate the filter and the antenna into a single module that achieves filtering and radiating functions at the same time, known as filter-antenna. Integration of microstrip filter and microstrip antenna represents a challenge for many researchers. The filter-antenna circuit suffers from some design problems that affect its performance. These problems were the main reasons for the variation between the simulation and experimental results. This study presents two different types of microstrip filter-antenna structures. It is the effort to improve the performance characteristics of the single-band filter-antenna and the dual-band filter-antenna. A single-band, dual-mode filter-antenna was designed using a Chebyshev lowpass prototype with passband ripple of 0.1 dB and fractional bandwidth (FBW) of 10.5 %, which operates at a centre frequency of 5.794 GHz. The measured of the filter-antenna is better than -21 dB. This microstrip filter-antenna is designed by using the modified shaped dual-mode square open-loop resonator structure. These types of resonators behave as a double tuned circuit. This new design not only reduces the circuit size of about 50 % as compared with the single-mode resonators, but also got the crucially less insertion loss. The single-band, dual-mode filter-antenna design is then modified by using U-shaped slot etched on the patch antenna to improve its performance. This filter-antenna is suitable for portable communication applications; because of its compact size of 22 x 22 x 1.6 mm3. The folded Stepped Impedance Resonator (SIR) dual-band filter-antenna was designed using Butterworth lowpass prototype. The measured fractional bandwidth for the first frequency band is 24.37 % and the measured fractional bandwidth for the second frequency band is 17.24 %. The measured first frequency passband of the filter antenna operates at a centre frequency of 5.75 GHz, and the measured second frequency passband operates at a centre frequency of 8.35 GHz. The measured of the first frequency passband is better than -24 dB, and of the second frequency passband is better than -15 dB. The folded SIR dual-band filter-antenna is designed by using four-folded SIR, where any two-folded SIR is connected together. These folded SIR are used instead of the conventional SIR to miniaturize the overall circuit size. The folded SIR dual-band filter-antenna is designed, and then modified by using the dumbbell-shaped Defected Ground Structure (DGS) to improve the filterantenna performance and for further reduce the size of the circuit. The dual-band filterantenna is suitable for mobile communication because of it is compact size of 41.4 30 1.6 mm3. The comparison of the simulated and measured S11-parameters of the folded SIR dual-band filter-antenna shows an acceptable matching between the simulation results and experimental results. The centre frequency of the first frequency passband is moves down from 5.8 GHz to 5.75 GHz and the centre frequency of the second frequency passband is shifted from 8.184 GHz to 8.35 GHz. This frequency shifting is due to the difference in the design component values of the theoretical and the practical design. Some comparisons have been made between the proposed designs and other literature works, also among some literature works for both single-band and dual-band filterantennas. The aim of these comparisons is to investigate the achievement of the research objectives. Single-band, dual-mode filter-antenna is compared with other filter-antennas literature works such as Ref. [85] and Ref. [109]. The specification and design comparison show that the proposed filter-antenna has a good design performance such as insertion loss, return loss, gain, and band edge selectivity. The proposed single-band, dual-mode filter-antenna has a circuit size reduction as compared with the circuit of Ref. [85] of about 50 %, and 70 % as compared with the circuit of the Ref. [109]. The design comparison of the proposed dual-band, folded SIR filter-antenna and other literature works such as Ref. [110], Ref. [89], and Ref. [111] shows that the proposed filterantenna has good design performance and good band edge selectivity. The proposed dual-band, folded SIR filter-antenna has a circuit size reduction as compared with the circuit of Ref. [110] more than 85 %, and 43 % as compared with the circuit of the Ref. [89]. The single-band, dual-mode filter-antenna is designed and fabricated to cover the Worldwide Interoperability for Microwave Access (WiMAX) application. Based on IEEE 802.16-2005 (802.16e), this technology supports mobility networking between the fixed base station and mobile devices. In addition, enables high signal speed required for communications with users moving by vehicles to have speed which is below 100 km/h. This technology provides symmetric bit rates of 70 Mbps and operates in the frequency range 2-6 GHz. The folded SIR dual-band filter-antenna is designed and fabricated to cover a Wireless Local Area Network (WLAN) application (5.75 GHz) for the first frequency passband and X-band (8-12GHz) applications for the second frequency passband. Satellite communication operates in part of the Xband or Super High Frequency (SHF) spectrum which is specified by (ITU). Satellite communication has the frequencies in the range 7.25 GHz to 7.75 GHz (space to earth) and 7.9 GHz to 8.4 GHz (earth to space). The main contributions of this study represented by the design and fabrication of a new structure single-band, dual-mode filter-antenna which used a novel shaped of the dual-mode resonator. The dual-mode resonator has highly contributed to the overall circuit size reduction and improved its band edge selectivity. In addition, the design of a new dual-band filter-antenna structure which used folded SIR and defected Ground Structure (DGS) are for more size reduction and band edge selectivity improvement. Single-band and dual-band microstrip filter-antennas are developed and analyzed using 3-D Computer Simulation Technology electromagnetic simulator software (CST). In order to verify the simulation results, the single-band filter-antenna and the dual-band filter-antenna are fabricated on FR-4 epoxy glass substrate material with a dielectric constant of 4.3 and loss tangent 0.02. The experimental measurements are carried out by using a Vector Network Analyzer (VNA Anritsu 37347D). The design of the filter-antenna models are fabricated and tested. A good agreement was found between simulated and measured results. The results were also compared to previous work to show the uniqueness of the design process implemented in the present work. All the objectives of the study have been achieved with a significant improvement in the performances of the proposed filter-antennas compared with previous works.